Blood eosinophil count (BEC) and fractional exhaled nitric oxide (FeNO) for steroid stewardship in chronic obstructive pulmonary disorder (COPD): A systematic review - Aditi Dhawan; Shruti Ayyalasomayajula; Mohammed Salim Karattuthodi; Mohan K. Manu; Mohamed Hisham; Javedh Shareef; Sathvik B. Sridhar (Elsevier, 2024)
Introduction: Chronic Obstructive Pulmonary Disorder (COPD) was estimated to be the sixth leading cause of death in 2019, and second most common cause of non-communicable disease-related deaths in India. Systemic or inhaled corticosteroid use must be assessed against any known toxicities risk to determine potential benefits. Thus, there should be a system to streamline the utilization of corticosteroids in COPD patients. Objective: To highlight the potential of clinical markers in promoting steroid stewardship. Additionally this study also emphasizes the need to identify more clinical markers that could determine steroid efficacy and help in tailoring the therapy for patients with COPD. Methodology: Two independent researchers conducted a systematic review to recognize the markers affecting COPD therapy. A literature search was conducted using a thorough search strategy, including search terms "COPD," "corticosteroids," "biomarkers," and related MeSH terms to recruit all relevant literature between 2007 and 2023. In total, 919 PubMed, Embase, and Scopus articles were screened, and 16 were finalized. Results: After thoroughly screening articles, two biomarkers were identified from the review. The majority (n = 13) stated that blood eosinophil count (BEC) could impact steroid therapy in COPD patients, further strengthened by the latest Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines. Fractional Exhaled Nitric Oxide (FeNO) is another component captured from (n = 3) studies presenting its benefit in directing corticosteroid therapy in COPD patients. Conclusion: This study showed that with an understanding of patient history, using BEC and FENO to determine steroid therapy in COPD could benefit. Although more studies are required, it is believed these markers can individualize steroid therapy, leading to better patient care and shaping the core of the steroid stewardship program.